(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Debates and discussions have long been essential in university education, yet technological advancements have transformed their preparation, organisation, and evaluation. Historically, public discourse was limited to experts or those with social status. Today, digital platforms provide this opportunity to everyone, aligning with the creative society paradigm. However, this accessibility has blurred the distinction between free expression and structured debate skills. Although freedom of speech is a democratic right, it does not guarantee the ability to engage in meaningful discussions. Therefore, it is especially important to pay attention to teaching of debates and discussions or learning through discussion and debating in universities. Various digital platforms incorporate algorithm-based tools for learning and discussion, but they often lack effectiveness, adaptability, and popularity. Mechanised tools developed without research are not effective and do not address the needs of the target audience. Therefore, the development of any machine learning tool, algorithm or platform should start with an experiential study of the target group. This study investigates what motivates students to actively engage in virtual discussions and what platform features encourage their sustained participation. An empirical study was conducted with 61 first-year PhD students (average age: 31). They watched three movies, formulated discussion questions, and participated in online debates via Moodle. Subsequently, they reflected on their experiences and identified key engagement factors, which were categorized into seven themes: Meaning Construction; Topic Features; Task-Related Requirements; Requirements for Virtual Discussion Platform; Virtual Discussion Activity; Nature and Structure of Communication; Social Interaction. The findings indicate that students are more active when the discussion topics are clear, directly related to their studies, and thought-provoking. Some students participate only due to assessment requirements, preferring in-person interactions. The study also highlights the growing issue of digital loneliness and the importance of fostering strong social connections in online learning environments. Additionally, an intuitive and visually appealing platform strengthens engagement, as students prefer tools that require minimal effort to navigate. Emotional connection with other PhD students, prompt responses from peers, and visible participant profiles further contribute to active participation. These insights are essential for designing effective virtual learning environments. The study highlights the necessity of user-centred design, which ensures that online platforms are not only functional but also foster meaningful engagement, social interaction, and enriching learning experience.